Application of recycled concrete aggregates and crushed bricks on permeable concrete road base. Issue 10 (3rd October 2021) - Cai, Xu; Wu, Kuanghuai; Huang, Wenke; Yu, Jiangmiao; Yu, Huayang
Abstract : Application of recycled concrete aggregates (RCA) and crushed bricks (CB) into pavement materials is an ideal waste management solution. By appropriate material design, the RCA and CB could be used in permeable concrete as the pavement base which meets the principle of 'sponge city'. This study aims to evaluate the performance of cement treated permeable concrete containing RCA and CB as the road base. Because of high-water absorption of RCA and CB leads to greater design deviations and resulted in leakage of cement slurry, the optimised volume method was used in mixture design. The compressive strength test, shrinkage test and water permeability test were performed. Results showed that the cement treated permeable concrete containing CB was an ideal fast-drying and low shrinkage due to drying material. Although CB had certain weakening effect on concrete strength, the strength of the permeable concrete was found acceptable according to the available specification. In addition, satisfied permeable performance was observed. It was recommended that concrete containing 15% of CB in weight (CB-15) was suitable to road base with moderate traffic level, and the concrete without CB (CB-0) to high traffic level, respectively. As the concept of environmental protection was being recognised by most countries in the world. This study suggested a potential direction for the large-scale application of RCA and CB.